A meridional 14C and 39Ar section in northeast Atlantic deep water - Schlitzer, Reiner; Roether, Wolfgang; Weidmann, Urs; Kalt, Peter; Loosli, Heinz Hugo (Journal of Geophysical Research, 1985)
14C, 39Ar, and complementary hydrographic and nutrient data are presented for deep water below 2500 m depth, from stations along a meridional section (8°S to 45°N) through the Romanche Trench and along the deep northeast Atlantic basins (F/S Meteor, cruise 56, leg 5). The large-scale 14C distribution along the section is resolved at the 14C data precision of ±2‰. Bottom water Δ14C decreases by 6‰ from the equator to 45°N, and farther up there is a weak Δ14C minimum (−123‰) over much of the section. The 14C data are interpreted as giving a turnover time of about 30 years for the waters below the depth of the 14C minimum (∼4250 m). It is found that water of 1.50±0.05°C potential temperature enters the East Atlantic from the west through the Romanche Trench (sill depth about 4000 m), and a preliminary value for the inflow rate of 3.6×106 m3/s is deduced. This rate greatly exceeds estimated deep inflow rates through the Vema fracture zone or across the northern boundary of the East Atlantic. 39Ar data that cover an entire deep-ocean circulation system are presented for the first time. The observed 14C and 39Ar distributions are mutually consistent. Transit times from the source regions to the equator for water from northern and southern deepwater sources are estimated to be about 170 and 105 years, respectively, and the 39Ar concentration of young Antarctic Bottom Water is deduced as 60±7% modern. The 39Ar-14C correlation in the ocean appears to be affected by mixing of waters of different age and by more efficient raising of 39Ar in the deepwater formation processes.